La semántica de la muerte: representación del Tánatos en Extracción de la piedra de locura, de Alejandra Pizarnik - Fernando Candón-Ríos (Confluenze)
This paper examines the manifestations of the death drive in Alejandra Pizarnik's work, Extracción de la piedra de locura (1968). When the Argentine poet selected the poems that make up this work, she chose texts developed between 1962 and 1964. Extracción represents her mature collection, while concurrently revealing the severe existential crisis of the author. The analysis of the verses demonstrates a tendency towards self-destruction and death. However, it starts from the initial hypothesis that the poetry collection is a confessional text, not a suicide note.